Psychological responses and coping mechanism of sexually abused teenagers: basis for psychiatric nursing care - Ubalde .T, Jumar (Universiti Kebangsaan Malaysia, 2011)
This study was undertaken to provide basis for the “Psychological Response and Coping Mechanism of Sexually Abuse Teenagers: A Basis for Psychiatric Nursing Care” which discover the different responses and coping mechanism of sexually abused teenagers. Respondents (50) were from the government institutions supervised by the Department of Social Welfare and Development (DSWD) namely residents of Marillac Hills at Town Center North Gate Avenue, Filinvest, Corporate City, Alabang, Munting Lupa City. Age of the respondents from 11-17 years old was included as the subject of the study. The study used a descriptive correlation research. The instrument used was a personal information sheet which includes their demographic variables, relationship to the Perpetrator, and reason for abused. Statistical measurements used are measures of Central Tendencies and Kruskall Wallis Two Way Anova by Ranks. This determines the respondents of the sample as to different area of functioning and coping mechanism. Also establish differences and correlation between two age groups (11-14 and 15-17 years old) based on the mentioned mechanism. In conclusion, the age group ratio was 3:1 (for 11-14 and 15-17 years old) distributed nationally from four regions of the country. Occupations of the parents were of blue-collar nature (driver, laborer, house maid) belong to the low socio-economic income of the society. Respondent educational attainment falls only up to the primary level of education. Majority of the respondents were abused by their father while other of their family relatives indicating that occurred within the household where the perpetrator tended to have close family relation with the victim. Result show there is no significant difference among the selected sexually abused teenagers when grouped as to birth of origin, father nature of work and five categories of coping mechanism. Based on the findings of the study, special programs for sexually abused teenagers should be conducted by the agency concerned and assisted by the NGO’s (the government centers). Their rights under the existing laws, victims of sexually abused women should be observed and respected. The center/ agency in charge of sexually abused teenagers provide assistance for them to continue their education, constant counseling, ensure reintegration in their family and community. That the agencies in-charge of keeping peace and order should enforce strictly rules in order to avoid/or minimize sexual abused. Further study maybe conducted in other agencies.